Influence of Brand Ambassador, Korean Wave And Promotion on Product Purchase Interest Somethinc in the Semarang City Community - Ulya’izah, Haniyah; Purwanto, Edy (Economics and Business International Conference Proceeding, 2024)
This study uses a type of quantitative research with multiple linear regression analysis methods and accidental sampling. Furthermore, data collection procedures include making questionnaires and analyzing data using SPSS 20 by testing validity, reliability, classical assumptions, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that all independent variables, namely brand ambassador (X1), promotion (X3), have a positive and significant effect on buying interest (Y); on the other hand, the Korean wave (X2) has no effect and is significant to buying interest (Y) partially and simultaneously. Based on the coefficient of determination of 0.501, the brand ambassador, Korean wave, and promotion variables account for 50.1% of the purchase intention variable. Other variables outside those not explained in this study accounted for 49.9% of the total.